Risk Factors Associated with Prostate Hyperplasia at Prof. Dr. W.Z. Johannes Hospital - Misnadin, Indri W.; Adu, Apris A.; Hinga, Indriati A. Tedju (Indonesian Journal of Medicine, 2016)
Background: The increase of Indonesiaâs population life expectancy causes the increase of advanced age people. This issue resulted in increasing of degenerative diseases such as Hyperplasia Prostate which is the second biggest disease in urology clinic in Indonesia. This study aimed to determine the risk factors in the form of age, smoking, alcoholic consumption, physical exercise, cholesterol, and diabetes mellitus associated to hyperplasia prostate cases at Prof.Dr. W. Z. Johannes, Hospital Kupang.Subjects and Method: This was an observational analytic study with case-control design. A total of the samples were 68 men were collected by random sampling technique. Dependent variable was prostate hyperplasia. Independent variables were age, smoking, phisycal exercise, alcohol consumption and diabetes mellitus. The data were analyzed by Chi-Square.Results: This research showed that risk associated the risk factors were age (OR=12.63; 95% CI= 2.60 to 61.37; p<0.001), smoking (OR=3.52; 95% CI=1.27 to 9.7; p=0.026), physical exercise (OR=3.38; 95%CI=1.25 to 9.16; p=0.014), and cholesterol level (OR=3.88; 95%CI= 1.41 to 10.66; p=0.007). There was no association on alcohol consumption (OR= 1.33; 95% CI= 0.47 to 3.78; p=0.595) and diabetes mellitus (OR=0.88; 95% CI=0.32 to 2.39; p=0.798). Â Conclusion: Increase prevention efforts such as screening prostate-specific antigen socialization and non-communicable diseases as a prevention in the future.Keywords: prostate hyperplasia, risk factorsCorrespondence:Â Indri W.Â Misnadin, Apris A.Â Adu, Indriati A.Â Tedju Hinga. Epidemiology and Biostatistics, School ofÂ  Public Health, Universitas Nusa Cendana, KupangIndonesian Journal of Medicine (2016), 1(1): 50-57https://doi.org/10.26911/theijmed.2016.01.01.07